The Role of Mesenchymal Stromal Cells-Derived Small Extracellular Vesicles in Diabetes and Its Chronic Complications - Li, Fu-Xing-Zi; Lin, Xiao; Xu, Feng; Shan, Su-Kang; Guo, Bei; Lei, Li-Min; Zheng, Ming-Hui; Wang, Yi; Xu, Qiu-Shuang; Yuan, Ling-Qing (Frontiers in Endocrinology, 2021)
Mesenchymal stromal cells (MSCs) are applied in regenerative medicine of several tissues and organs nowadays by virtue of their self-renewal capabilities, multiple differentiation capacity, potent immunomodulatory properties, and their ability to be favourably cultured and manipulated. With the continuous development of “cell-free therapy” research, MSC-derived small extracellular vesicles (MSC-sEVs) have increasingly become a research hotspot in the treatment of various diseases. Small extracellular vesicles (SEVs) are membrane vesicles with diameters of 30 to 150 nm that mediate signal transduction between adjacent or distal cells or organs by delivering non-coding RNA, protein, and DNA. The contents and effects of sEVs vary depending on the properties of the originating cell. In recent years, MSC-sEVs have been found to play an important role in the occurrence and development of diabetes mellitus as a new way of communication between cells. Diabetes mellitus is a common metabolic disease in clinic. Its complications of the heart, brain, kidney, eyes, and peripheral nerves are a serious threat to human health and has been a hot issue for clinicians. MSC-sEVs could be applied to repair or prevent damage from the complications of diabetes mellitus through anti-inflammatory effects, reduction of endoplasmic reticulum-related protein stress, polarization of M2 macrophages, and increasing autophagy. Therefore, we highly recommend that MSC-sEVs-based therapies to treat diabetes mellitus and its chronic complication be further explored. The analysis of the role and molecular mechanisms of MSC-sEVs in diabetes and its related complications will provide new idea and insights for the prevention and treatment of diabetes.